Impact of Surgery on Growth, Pulmonary Functions, and Acute Pulmonary Exacerbations in Children with Non-Cystic Fibrosis Bronchiectasis - Emiralioglu, Nagehan; Dogru, Deniz; Yalcin, Songul; Tugcu, Gokcen Dılsa; Yalcin, Ebru; Ozcelik, Ugur; Ekinci, Saniye; Kiper, Nural (The Thoracic and Cardiovascular Surgeon, 2019)
Background Treatment decisions for the management of bronchiectasis include medical treatment, such as antibiotics, chest physiotherapy, and surgical procedures. Here, we aimed to review the effect of lung resection on longitudinal growth, clinical course of patients depending on annual exacerbation rates, and pulmonary function tests (PFTs) and compare them with the results of only medically treated children with non-cystic fibrosis (non-CF) bronchiectasis.Methods The medical records of patients with non-CF bronchiectasis were retrospectively analyzed. Patients who underwent lobectomy/segmentectomy/pneumonectomy were categorized as “surgery group” (n = 29). Age- and gender-matched patients who were only medically treated were selected as “medical group” (n = 33). Annual data of patients were included till the end of postoperative second year in the surgery group and third year of medical treatment in the medical group.Results Mean baseline height z-score was lower in the surgery group, and mean baseline PFT values were all lower in the surgery group than those in the medical group (p < 0.05). In the surgery group, mean values of height z-score were –1.68 ± 0.92 at the time of surgery and improved to –1.42 ± 1.22 and –1.34 ± 1.05 in the first and second postoperative years, respectively, and annual intravenous antibiotic requirements decreased significantly (p < 0.05); however, mean body mass index (BMI) z-score values and PFT parameters did not change significantly. In the medical group, height z-score mean values and PFT parameters showed nonsignificant improvement but annual exacerbation frequency, annual intravenous, and oral antibiotic requirements decreased significantly.Conclusion Surgical management of non-CF bronchiectasis has no significant effect on BMI z-scores, annual exacerbation frequencies, oral antibiotic requirements and lung function tests; but can lead to significant improvement on height z-scores and decrease need of annual intravenous antibiotic requirements for acute severe exacerbations despite small number of patients in this study.
Keywords: non-CF bronchiectasis; surgery; medical treatment; pulmonary exacerbation